Evaluation of landfill management at Piyungan landfill Yogyakarta by using integrated risk based approach method - Mayasari, Hani; Wardhana, Banu Iqra; Tahir, Iqmal (Journal of Environmental Engineering and Landscape Management, 2023)
The volume of domestic waste in the Special Region of Yogyakarta (DIY Region) during the last five years has increased significantly by 34%, while the volume of waste handled has only increased by 8%. The average produced waste was 1,008.26 tonnes/day, while the handled waste reached 642.01 tonnes/day. That means 366.25 tonnes of unhandled waste per day, resulting in environmental pollution. This paper aims to evaluate the management of the Piyungan landfill by using the Integrated Risk Based Approach (IRBA). IRBA is a tool of decision-making created in 2005 for landfill rehabilitation, including sites with high health risks, maximum environmental impacts, and sensitive public concerns. A total of 26 parameters were used to evaluate the landfill and waste management in the Piyungan landfill site. The Risk Index (RI) calculated using the IRBA method shows that the final result of the Piyungan landfill was 649.76. The value of RI indicated a potential for high hazard, and the landfill must be closed immediately because it pollutes the environment or causes social problems. The factual conditions in the field indicate that technical age and capacity are serious problems faced with concern with the management of waste for the Yogyakarta, Sleman Regency, and Bantul Regency as Piyungan landfill users.